FBXO5 acts as a novel prognostic biomarker for patients with cervical cancer - Jiang, Shan; Zheng, Jianfeng; Cui, Zhaolei; Li, Yanhong; Wu, Qiaoling; Cai, Xintong; Zheng, Chaoqiang; Sun, Yang (Frontiers in Cell and Developmental Biology, 2023)
Background: Cervical cancer (CESC) remains one of the most common and deadly malignancies in women worldwide. FBXO5, a protein-coding gene, is highly expressed in a variety of primary tumors and promotes tumor progression, however, its role and prognostic value in CESC remain largely unknown. Methods: A key differential gene, FBXO5, was screened according to WGCNA based on immunohistochemical assays of clinical samples, multiple analyses of the Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases, including survival analysis, tumor mutational burden, GO, KEGG, tumor immune infiltration and chemotherapeutic drug sensitivity, to explore the expression and prognostic value of FBXO5 in CESC. The migration and invasiveness of cervical cancer cells following FBXO5 silencing and overexpression were examined using wound healing and Transwell assays, and the viability of cancer cells was assessed using CCK8 and EdU assays. Results: FBXO5 was discovered to be substantially expressed in CESC tissues using data from our CESC cohort and the TCGA database, and a survival analysis indicated FBXO5 as a predictive factor for poor overall survival in CESC patients. In vitro, CESC cells were more inclined to proliferate, migrate, and invade when FBXO5 was upregulated as opposed to when it was silenced.